A Comparative Study of the Age of Criminal Liability for Children in Islamic and Pakistani Law - Dr.Saleem Raza; Dr.Abdu-Haye Abro; Dr.Muhammad Hamid Raza; Dr.Abdul Hameed; Dr. Nasir Amin; Dr.Muhammad Qasim Siddiqi (Al-Qanṭara, 2023)
The concept of criminal liability for a child is an important and complex issue in Islamic and Pakistani law. In Islamic law, there is a stage called "mukhaffafa" which reduces criminal responsibility from the age of seven to fifteen years. During this stage, the judge is given discretion to decide on disciplinary measures based on the child's understanding and awareness. Islamic law also allows for measures to be taken for the rehabilitation of the child, taking into account psychological, economic, and social factors. In Pakistani law, the determination of the implementation of disciplinary measures is solely based on legal procedures, and there is no such stage as "mukhaffafa." However, Pakistani law recognizes the need for child’s rehabilitation and has legal provisions for this purpose. The comparative study of Islamic and Pakistani law reveals some similarities and differences. While both systems recognize the need for the child’s rehabilitation, Islamic law places greater emphasis on the psychological and social factors of the child, while Pakistani law focuses more on legal procedures. Additionally, Islamic law has a specific stage of mukhaffafa, while there is no such stage in Pakistani law. Overall, the criminal liability of a child is a complex issue that requires a balanced approach that considers both the legal procedures and the rehabilitation needs of the child. While Islamic and Pakistani law have different approaches, both systems recognize the importance of rehabilitating children who have committed crimes.